Histiocytosis: An Uncommon Presentation with Hypopituitarism - Kota, SK; Jammula, S; Tripathy, PR; Kota, Siva Krishna; Meher, LK; Modi, K (Journal of Nepal Paediatric Society, 2012)
Langerhans cell histiocytosis is a multi system disorder with a certain predilection for involving hypothalamic pituitary axis. We hereby report a 7 year old girl presenting with polyuria, polydipsia and growth retardation. The girl had a past history of pain in right hip joint and nodular region over chest. Water deprivation test confirmed the diagnosis of central diabetes inspidus. Other investigations revealed Growth hormone deficiency and central hypothyroidism. X-ray and MRI hip revealed absent right inferior pubic ramus with bone marrow biopsy confirming the diagnosis of histiocytosis. Patient was treated with nasal Arginine Vasopressin spray, subcutaneous growth hormone and oral thyroxine. Key words: Histiocytosis; Diabetes inspidus; Growth hormone deficiency; Central hypothyroidism DOI: http://dx.doi.org/10.3126/jnps.v32i1.5343 J. Nepal Paediatr. Soc. Vol.32(1) 2012 81-84